Kreatif Menanam, Asyik Mendaur Ulang di SD Palalangan 2, Kecamatan Cermee, Kabupaten Bondowoso - Shinta Yama Diwipa; Adella Mutia Devi; Ahsan Sutio Ivandi; Devan Eka Iswahyudi; Rio Raditiya Ardiyansah; Azizah Nur Laili; Moh Rois Fawwaz; Oria Alit Farisi; Dwi Erwin Kusbianto; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Education serves as a vital factor in society, forming the foundation for shaping children's character and personality. A social project was implemented to provide knowledge to elementary school children at SD Palalangan 2, Cermee District, Bondowoso Regency, involving all students from grades 1 to 6. The program included: pre-test, introduction to plant parts, instruction on planting kale using soil media, knowledge on reusing containers, kale plant maintenance, educational games about plant parts, and post-test. The social project entitled